MANAJEMEN KURIKULUM SEBAGAI PENGEMBANGAN TUJUAN PENDIDIKAN - Nanang Qosim; M. wildan maulana; Wasiatul ana (Universitas Sains dan Teknologi Komputer, 2023)
Project planning (planning), organizational activities(organizing), implemention activities (actuating, and control activities (controlling) all seem to be elements of science and art in management. Call on the help of others and use all available resources to achieve the preveous goal. Preparing, implementing,and analyzing the current curriculum are all elementsof the event wich is known as curriculum management. National education goals are national goals thats must be achieved and are also based on a national philosophy. This Destiny is complete, full, and functions as the parent of the purposes to which it is also subordinate.